Cold-adapted enzymes produced by fungi from terrestrial and marine Antarctic environments. (19th May 2018) - Duarte, Alysson Wagner Fernandes; dos Santos, Juliana Aparecida; Vianna, Marina Vitti; Vieira, Juliana Maíra Freitas; Mallagutti, Vitor Hugo; Inforsato, Fabio José; Wentzel, Lia Costa Pinto; Lario, Luciana Daniela; Rodrigues, Andre; Pagnocca, Fernando Carlos; Pessoa Junior, Adalberto; Durães Sette, Lara
Abstract: Antarctica is the coldest, windiest, and driest continent on Earth. In this sense, microorganisms that inhabit Antarctica environments have to be adapted to harsh conditions. Fungal strains affiliated with Ascomycota and Basidiomycota phyla have been recovered from terrestrial and marine Antarctic samples. They have been used for the bioprospecting of molecules, such as enzymes. Many reports have shown that these microorganisms produce cold-adapted enzymes at low or mild temperatures, including hydrolases (e.g. α-amylase, cellulase, chitinase, glucosidase, invertase, lipase, pectinase, phytase, protease, subtilase, tannase, and xylanase) and oxidoreductases (laccase and superoxide dismutase). Most of these enzymes are extracellular and their production in the laboratory has been carried out mainly under submerged culture conditions. Several studies showed that the cold-adapted enzymes exhibit a wide range in optimal pH (1.0–9.0) and temperature (10.0–70.0 °C). A myriad of methods have been applied for cold-adapted enzyme purification, resulting in purification factors and yields ranging from 1.70 to 1568.00-fold and 0.60 to 86.20%, respectively. Additionally, some fungal cold-adapted enzymes have been cloned and expressed in host organisms. Considering the enzyme-producing ability of microorganisms and the properties of cold-adapted enzymes, fungi recovered from Antarctic environments could be a prolific genetic resource for biotechnological processes (industrial and environmental) carried out at low or mild temperatures.